Optical solitons to the fractional perturbed Radhakrishnan-Kundu-Lakshmanan model - Sulaiman, Tukur Abdulkadir; Bulut, Hasan; Yel, Gulnur; Atas, Sibel Sehriban (Springer, 2018)
This study reaches the dark, bright, mixed dark-bright, singular, mixed singular optical solitons and singular periodic wave solutions to the time-fractional Radhakrishnan-Kundu-Lakshmanan equation. The parametric conditions that guarantee the existence of valid solitons and other solutions are stated. By choosing some suitable values of parameters, the 2- and 3-dimensional surfaces to some of the reported solutions are plotted. The reported solutions may be useful in expalining the physical meaning of the Radhakrishnan-Kundu-Lakshmanan equation and other related nonlinear models arising in nonlinear sciences.
Keywords: Sinh-Gordon equation; Optical soliton; Fractional derivative